Kompetensi Kepribadian Guru Dalam Menumbuhkan Nilai-Nilai Nasionalisme Siswa Pada Mata Pelajaran SKI Di MTs Al-Mustofaiyah Sukaresmi Garut - Salamudin, Ceceng; Evi Saefuloh, Dede (STAI Al-Musaddadiyah Garut, 2022)
The current state of national character in Indonesia is deeply concerning. Society, including students, is increasingly influenced by teachings that contradict the values of Pancasila, leading to a decline in nationalism. Key issues among students include indifference towards their peers' difficulties, lack of discipline in studying, and a preference for foreign cultures over their own. The personal competence of teachers is crucial in addressing these issues. Teachers who exemplify positive attitudes related to nationalism can effectively foster a sense of nationalism in their students. This is because teachers not only impart knowledge but also serve as role models through their attitudes, words, and actions. The purpose of this study is to describe the profile of teacher personal competence and its implications for the development of nationalism values among students in the SKI (Islamic Cultural History) subject at MTs. Al-Mustofaiyah Sukaresmi Garut. This research employs a descriptive method, utilizing data collection techniques such as observation, interviews, and document studies. The data analysis technique used is content analysis, with data validation performed through triangulation. The results indicate that teachers' role modeling in the educational process effectively fosters nationalism values in students, such as mutual assistance, discipline, patriotism, bravery, and honesty. Keywords: Teacher Personal Competence, Nationalism Values, Islamic Cultural History